Levels of modalization in existential and transcendental analysis: The matter of being-in-self - Rosato, Paolo (Interdisciplinary Studies in Musicology, 2018)
This essay reflects on some applications of Eero Tarasti’s existential semiotics to music analysis, starting from the asymmetry that marks the categories of “myself’ and “itself’. If it seems evident that we can know the musical being-in-itself, that is topics, norms, forms, and so on, we can wonder if and how we can know the being-in-myself, that is the pure kinetic energy before that it has token any kind of forms. As it is for Schopenhauer’s “Wille”, that firstly becomes objective as Platonic ideas, and secondly as spatio-temporal-causal natural realm; musical energy or “being-in myself’ takes shape firstly as virtual deep-level-figures, and secondly as spatio-temporal-actorial situations, within which being-for-myself struggles with the being-for-itself. Modalities (will, must, can, know) operate in both these two levels of taking shape, but at the first level we have to look for a transcendental musical subject, not characterized by specific historical and cultural features. Then, I introduce the notion of homeostasis, that is the principle that “regulates the global process of breaking away from an original state of rest or balance, and of the subsequent restoration of that balance”. Homeostasis allows us to analyze musical modalization at a deep level, where the transcendental subject takes the form of the being-in-itself. But the research of a transcendental subject is slightly different to that of the Moi, within which the being-in-myself is situated. To analyze the being-in-myself of an individual musical subject, we adopt a less universal homeostasis, that is a specific way to convey musical energy (melodic, harmonic, rhythmic, agogic, and so on) proper of Western music. So doing, I claim that one cannot recognize the first four measures of Beethoven’s Piano Sonata op. 7 as “the moment of Being-in-myself in all of its immediacy” as Tarasti does. Being-in-myself has to be examined in a different light.